Long‐term functional outcome of colonic resections: how much does faecal impairment influence quality of life?. (3rd November 2016) - Magdeburg, J.; Glatz, N.; Post, S.; Kienle, P.; Rickert, A.
Abstract: Aim: Older data suggest that colonic resection has a negative impact on continence and quality of life. The aim of this study was to evaluate the functional outcome of colonic resections for colonic cancer and diverticulitis and its influence on quality of life. Methods: Patients who underwent colonic resection between 2005 and 2013 were identified from a prospective database. A survey with two questionnaires [Faecal Incontinence Quality of Life (FIQL) scale, Short Form 12 (SF‐12)] and additional questions concerning bowel function was sent to all patients. Results: Colonic resection was performed in 362 patients in the study period; 297 patients returned the questionnaires (response rate 82.0%). Faecal urgency or incontinence more than once a month was present in 15% of patients and 25% of patients reported that bowel symptoms limited their quality of life. The mean total FIQL score for all patients was 3.58. The SF‐12 score was comparable to a reference population without prior colonic resection. Patients after right‐sided resections had liquid stool more often than others (45.3% vs 38.7%, P  =   0.011). No differences in bowel function and quality of life were detected between resections for colonic cancer and diverticulitis. Conclusion: Most patients experience no limitation in bowel function after segmental colectomy. Those with limitations in bowel function still seem to cope well, as the quality of life is not severely affected. Nevertheless, most patients with lower functional scores also had lower quality of life scores. Whether surgery is a relevant factor has to be questioned, as the prevalence of faecal incontinence in a comparable population without prior surgery is almost identical.